Why do women still give birth at home; perceptions of Pakistani women and decision-makers from marginalized communities. - Ayesha Khalid; Kaniz Amna Haider; Hareem Ahmer; Sahir Noorani; Zahra Hoodbhoy (Public Library of Science (PLoS), 2023)
In low- and middle-income countries (LMICs), maternal and newborn mortality is high due to the high prevalence of home births. Understanding the reasons behind this behavior is essential for improving maternal and newborn outcomes. Therefore, a qualitative exploratory study was conducted in a peri-urban community in Karachi, Pakistan to understand the perceptions of pregnant women who delivered at home despite receiving antenatal care and the perceptions of their decision-makers regarding this behavior. In-depth interviews were conducted with 15 randomly sampled women who chose to deliver at home after receiving antenatal care at a health facility, as well as 15 family members who were purposively identified as decision-makers by the women themselves. Thematic analysis was performed to explore the perceptions, myths, and cultural beliefs about homebirths as well as women's decision-making power related to childbirth. The three main themes identified showed that traditional beliefs and practices, poverty and gender inequality, and poor healthcare systems significantly influence the preference for childbirth. Traditional beliefs and practices, including religious and cultural beliefs, played a role in perceiving childbirth as a natural process best managed at home. The presence of traditional birth attendants who provide personalized care and emotional support further reinforced this preference. Gender inequalities, including limited access to mobile phones and women's caregiving roles, were identified as barriers to seeking formal healthcare at the time of delivery. Additionally, poor experiences with the formal healthcare system, such as the poor attitude of formal healthcare workers and fear of medical interventions, also contributed to the decision to deliver at home. The study highlighted the complex interplay between traditional/religious beliefs, gender inequalities, and healthcare experiences in shaping the decision to deliver at home despite receiving ANC services in marginalized settings. Addressing these factors is necessary for promoting facility-based delivery and improving maternal and neonatal outcomes in LMICs.